Application of electroacupuncture for postoperative pain management after total knee arthroplasty: a study protocol for a single-blinded, randomised placebo-controlled trial - Ling Zhao; Sheng Zhong; Hai Huang; Jun Xie; Xiu-ling Song; Yue-lai Chen; Lian-bo Xiao (BMJ Open)
Introduction The purpose of this study is to assess the efficacy of electroacupuncture (EA) to relieve pain and promote functional rehabilitation after total knee surgery.Methods and analysis We propose a single-blinded, randomised placebo-controlled trial to evaluate the efficacy of EA. Patients with osteoarthritis (aged 55–80 years) undergoing unilateral total knee arthroplasty (TKA) will be included in the trial. They will be randomised to receive either EA or sham-EA. A total of 110 patients will receive EA and sham-EA for 3 days after TKA. Postoperative pain will be measured using visual analogue score, and the need for an additional dose of opioid and analgesics will be recorded as the primary outcome. Secondary outcomes include knee function and swelling, postoperative anxiety, postoperative nausea and vomiting among other complications.Ethics and dissemination This study has been approved by the ethics committee, and subsequent modifications of the protocol will be reported and approved by it. Written informed consent will be obtained from all of the participants or their authorised agents.Trial registration number ChiCTR1800016200; Pre-results.